Development planning at the coastal area by using unmanned aerial vehicle (UAV) image in Kuala Perlis / Wan Farhana Mohamad Ramli - Mohamad Ramli, Wan Farhana (2020)
Urban planning is described as a connection to plan and national plans. Coastal development has led to increasing land demand, particularly in developed areas. The coastal areas of today are facing intense issues created by rapid urbanization, coastal erosion increasing sea level, global warming, and climate change. The aim of this study is to produce a three-dimensional (3D) development planning design based on orthophoto image at the coastal area in Kuala Perlis. The objective is to generate the digital of orthophoto image using UAV aerial images and to produce development planning at Kuala Perlis based on orthophoto image. Study area that has been chosen is Kuala Perlis, Perlis State with cover area 1.13 km². This study involves three types of data which is interviewing with the government, Unmanned Aerial Vehicle (UAV) images data and Global Positioning System (GPS) observation which have five (5) Ground Control Points (GCPs). The Agisoft Metashape Professional software has been used to orient images, extract point clouds, construct a digital surface model (DSM) and create orthomosaic images. After that, digitize the orthophoto image by using AutoCAD then, import to sketch-up for 3D development. The final output in this study is a production of 3D development planning design which is attached from the digitizing of orthophoto images. The GCPs were used in this research is as an educational under the photogrammetry because it is only focus for development design. This method also can help Town Planner for the future development planning.